Mercury's Crustal Thickness Correlates With Lateral Variations in Mantle Melt Production. Issue 9 (29th April 2020) - Beuthe, Mikael; Charlier, Bernard; Namur, Olivier; Rivoldini, Attilio; Van Hoolst, Tim
Abstract: Over the first billion years of Mercury's history, mantle melting and surface volcanism produced a secondary magmatic crust varying spatially in composition and mineralogy. By combining geochemical mapping from MESSENGER with laboratory experiments on partial melting, we translate the surface mineralogy into lateral variations of surface density and calculate the degree of mantle melting required to produce surface rocks. If lateral density variations extend through the whole crust, the local crustal thickness correlates well with the degree of mantle melting. Low‐degree mantle melting produced a thin crust below the northern volcanic plains (19±3 km), whereas high‐degree melting produced the thickest crust in the ancient high‐Mg region (50±12 km), refuting the hypothesis of an impact origin for that region. The thickness‐melting correlation has also been observed for the oceanic crust on Earth and might be a common feature of secondary crust formation on terrestrial planets. Plain Language Summary: Mercury's crust has a complex structure resulting from a billion years of volcanism. The surface variations in chemical composition have been identified from orbit by the spacecraft MESSENGER. Combining these measurements with laboratory experiments on partial melting, we estimate which variations in surface density and degree of mantle melting are required to produce surface rocks. If the surface density is representative of the deep crustal density, more than one half of crustal thickness variations in the Northern Hemisphere are explained by lateral variations in mantle melting. The crust is thin below the magnesium‐poor northern volcanic plains, whereas the thickest crust is found in the magnesium‐rich region located at middle northern latitudes in the Western Hemisphere. The magnesium‐rich region is thus not due to an early impact but rather to extensive mantle melting. The thickness‐melting relation has also been observed for the oceanic crust on Earth and might be a common feature of terrestrial planets. Key Points: Maps of surface density, degree of mantle melting, and crustal thickness are inferred from geochemical and geodetic data We find a high correlation between lateral variations in Mercury's crustal thickness and mantle melt production The crust is thickest in the ancient high‐Mg region